Adolescentes em situação de pobreza: resiliência e vulnerabilidade às IST/HIV/AIDS - Costa, Maria Isabelly Fernandes da (2017)
Adolescence is a phase of life, permeated by transformations and initiation of sexual activity, which makes adolescents vulnerable to IST/HIV/AIDS. In this context, poverty represents a vulnerability that increases risks detrimental to health. Resilience in this sense presents itself as a possibility of reducing vulnerability, since it is characterized as a positive response in relation to overcoming the situation of risk, adaptation and personal empowerment. The objective was to analyze the relationship between vulnerabilities to IST/HIV/AIDS of adolescents living in poverty and their level of resilience. This is a cross-sectional, quantitative study conducted with 287 adolescents from the 6th and 7th years of elementary school at a public school in the city of Fortaleza, CE, between 11 and 17 years. Data collection took place in three stages - application of the socioeconomic questionnaire - application of the IST/HIV/AIDS vulnerability questionnaire - application of the resilience scale. Data were analyzed using SPSS, version 20.0 and presented in tables. The Mann-Whitney or KrusKal-Wallis test was used to assess the association between the biological and social factors of adolescents with the IST/ HIV/AIDS vulnerability questionnaire as well as the resilience scale. The association between the IST/HIV/AIDS vulnerability questionnaire and the scale was performed using the Spearman correlation coefficient, considering as statistically significant the analyzes with p <0.05. The study was approved with the opinion incorporated under no: 1.615.672. Of the 287 adolescents, 66.6% were male and 33.4% female. The predominant age group was the average adolescence, corresponding to ages between 15 and 16 years. It was observed that 40.8% of the adolescents had not yet had sex, although of those who had sexual intercourse, 38.3% did not use a condom in at least one of the relationships. Regarding condom use, 84% consider it good to avoid children, HIV and STIs, and 16.4% consider that it does not need to be used with the person they love and trust. The adolescents most vulnerable to IST/HIV/AIDS are males, between the ages of 11 and 12 years and 60 years without religion. In another type of relationship, living with six or more people. While the most resilient adolescents were female, between 17 and 18 years, of the 70 year without religion, living with two people. A statistically significant association was identified between the vulnerability questionnaire and the resilience scale, considering p = 0.022, with an inversely proportional relation with p=-0.135. It is concluded that the adolescents most vulnerable to IS/THIV/AIDS and less resilient are male, which implies the need for the nurse professional to carry out educational actions aimed at promoting the resilience and health of these adolescents.